EVALUATIONS OF BODY COMPOSITION AND GROWTH PERFORMANCE BY APPLYING DIFFERENT DIETARY VITAMIN C LEVELS IN ASIAN CATFISH, CLARIAS BATRACHUS (LINNAEUS, 1758) - HIMADRI PAL; DEBAJYOTI CHAKRABARTY (International Journal of Pharma and Bio Sciences, 2012)
Studies were conducted to determine the effects of high dietary ascorbic acid (vitamin C) on growth performance and body composition of a commercially important Asian catfish, Clarias batrachus. During experimental trial in the laboratory condition, the change in growth and feed utilization by the Clarias batrachus fed on three different Vitamin C level have been assessed by the determination of survival rate (SR), specific growth rate (SGR%), condition factor (K), feed conversion ratio (FCR), average daily gain (ADG) and protein efficiency ratio(PER). All the water quality parameters specifically- Temperature ( ), Dissolved oxygen (DO), Carbon dioxide (CO2) and pH in the plastic tanks were highly monitored and maintained. The highest food conversion ratio (FCR) was found in the treatment 1 while the lowest was measured in treatment 3. The values of protein efficiency ratio (PER), condition factor, average daily gain (ADG) and specific growth rate(SGR) were highest in treatment 3 and lowest in treatment 2 and treatment 1 respectively. Result of the current study showed that supplementation of Vitamin C at 1200 mg/kg feed had significant positive effects on the FCR, SGR, ADG, PER while no such differences were observed in condition factor variables. The fish Diet C containing 1200 mg/ kg of Vitamin C level has been found to be more effective for better growth of the Clarias batrachus.